Intersectional Lenses of DEI: Bioethicists’ Duty to Advocate - Boerstler, Jillian; Elster, Nanette; Parsi, Kayhan; Pilkington, Bryan (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
Building on the historical foundation of bioethics, we argue that bioethicists, with inherently interdisciplinary approaches and backgrounds, are well positioned to promote Diversity Equity and Inclusion (DEI) in the healthcare setting through the practice of clinical ethics. In the current cultural and political climate, bioethicists cannot remain silent while staying true to the tenets of the field. Provisions in the American Society for Bioethics and Humanities (ASBH) Code of Ethics and the lived experience of Canadian bioethicists offer relevant guidance. We argue that competence in clinical ethics obliges bioethicists to identify and seek to remove systemic barriers facing those whom clinical ethicists are privileged to serve. By adopting an intersectional approach to clinical bioethics, bioethicists can become advocates for the promotion of just healthcare.